Protential of wide- frequancy bandwith.. - Madhn Muthusamy (2023)
The study regarding piezoelectric energy harvester has been on the rise in recent years. Various studies have been conducted by researches to increase the bandwidth of frequency. Bandwidth is to be increased in order to increase the amount of data transferred per second to generate an efficient information and data transfer. Study has been conducted on the potential of wide frequency bandwidth piezoelectric energy harvester using springs and magnets. Experiment and simulation have been done to test the effect of magnet and spring on frequency bandwidth. Springs and magnets were manipulated throughout the experiment. Springs were manipulated in numbers and arrangements while magnets were manipulated by numbers and position. The experiments and simulations were conducted to measure the voltage gain due to manipulation of spring and magnets. The graph obtained is used to measure the bandwidth generated. Simulation has been done using COMSOL Multiphysics software. The results from experiment and simulation were compared to validate the results obtained.